Genetic Variability in Phosphorus Responses of Rice Root Phenotypes - Vejchasarn, Phanchita; Lynch, Jonathan P.; Brown, Kathleen M. (Rice (New York, N.Y.), 2016)
Background Low phosphorus availability is a major factor limiting rice productivity. Since root traits determine phosphorus acquisition efficiency, they are logical selection targets for breeding rice with higher productivity in low phosphorus soils. Before using these traits for breeding, it is necessary to identify genetic variation and to assess the plasticity of each trait in response to the environment. In this study, we measured phenotypic variation and effect of phosphorus deficiency on root architectural, morphological and anatomical traits in 15 rice ( Oryza sativa ) genotypes. Rice plants were grown with diffusion-limited phosphorus using solid-phase buffered phosphorus to mimic realistic phosphorus availability conditions. Results Shoot dry weight, tiller number, plant height, number of nodal roots and shoot phosphorus content were reduced under low phosphorus availability. Phosphorus deficiency significantly reduced large lateral root density and small and large lateral root length in all genotypes, though the degree of plasticity and relative allocation of root length between the two root classes varied among genotypes. Root hair length and density increased in all genotypes in response to low phosphorus. Nodal root cross-sectional area was significantly less under low phosphorus availability, and reduced cortical area was disproportionately responsible for this decline. Phosphorus deficiency caused a 20 % increase in the percent cortical area converted to aerenchyma. Total stele area and meta-xylem vessel area responses to low phosphorus differed significantly among genotypes. Phosphorus treatment did not significantly affect theoretical water conductance overall, but increased or reduced it in a few genotypes. All genotypes had restricted water conductance at the base of the nodal root compared to other positions along the root axis. Conclusions There was substantial genetic variation for all root traits investigated. Low phosphorus availability significantly affected most traits, often to an extent that varied with the genotype. With the exception of stele and meta-xylem vessel area, root responses to low phosphorus were in the same direction for all genotypes tested. Therefore, phenotypic evaluations conducted with adequate fertility should be useful for genetic mapping studies and identifying potential sources of trait variation, but these should be confirmed in low-phosphorus environments.